Effect of delayed graft function on longer‐term outcomes after kidney transplantation from donation after circulatory death donors in the United Kingdom: A national cohort study. Issue 10 (6th May 2021) - Phillips, Benedict L.; Ibrahim, Maria; Greenhall, George H. B.; Mumford, Lisa; Dorling, Anthony; Callaghan, Chris J.
Abstract : Kidneys from donation after circulatory death (DCD) donors are utilized variably worldwide, in part due to high rates of delayed graft function (DGF) and putative associations with adverse longer‐term outcomes. We aimed to determine whether the presence of DGF and its duration were associated with poor longer‐term outcomes after kidney transplantation from DCD donors. Using the UK transplant registry, we identified 4714 kidney‐only transplants from controlled DCD donors to adult recipients between 2006 and 2016; 2832 recipients (60·1%) had immediate graft function and 1882 (39·9%) had DGF. Of the 1847 recipients with DGF duration recorded, 926 (50·1%) had DGF < 7 days, 576 (31·2%) had DGF 7–14 days, and 345 (18·7%) had DGF >14 days. After risk adjustment, the presence of DGF was not associated with inferior long‐term graft or patient survivals. However, DGF duration of >14 days was associated with an increased risk of death‐censored graft failure (hazard ratio 1·7, p  = ·001) and recipient death (hazard ratio 1·8, p  < ·001) compared to grafts with immediate function. This study suggests that shorter periods of DGF have no adverse influence on graft or patient survival after DCD donor kidney transplantation and that DGF >14 days is a novel early biomarker for significantly worse longer‐term outcomes. Abstract : A large cohort study in donation after circulatory death donor kidney transplantation finds that delayed function lasting more than 14 days is a novel early biomarker for inferior graft and patient survival.